Melatonin attenuates thiocyanate-induced vasoconstriction in aortic rings - Alexander M. Prusa; Christian A. Plass (Saudi Pharmaceutical Journal)
Cigarette smoking not only has a carcinogenic effect but also leads to an increase in arterial blood pressure. Besides its main components, i.e. nicotine, tar, and carbon monoxide, cigarette smoke also contains thiocyanate. Thiocyanate anions (SCN−) arise from the detoxification of hydrogen cyanide and its plasma concentrations were found to correlate significantly with cigarette consumption. There is also evidence that atherosclerotic disease progression is much more rapid when serum SCN− levels are increased. Melatonin, a non-toxic indolamine with various physiologic functions, is believed to protect against inflammatory processes and oxidative stress. It has been demonstrated that melatonin serves as free radical scavenger and represents a potent antioxidant. Therefore, it is believed that melatonin with its atheroprotective effects may be useful either as a sole therapy or in conjunction with others. The aim of this study was to quantify the thiocyanate-induced vasomotor response in aortic tissue and further to examine the potential of melatonin in affecting the generated vasoreactivity. Aortic rings of adult male normotensive Wistar rats were cut into 4-mm rings. Following the administration of thiocyanate in various concentrations, vasomotor response of aortic vessel segments was measured. To assess the effect of melatonin on vasomotor activity, organ bath concentrations were modulated from 60 to 360 pM, which corresponds to physiologic plasma up to the levels of patients with regular oral intake of 3 mg of melatonin as a supplement. Thirty-six rat aortic rings were studied. When exposed to thiocyanate, vessel segments revealed vasoconstriction in a concentration-dependent manner. In rings which were preincubated with melatonin at a concentration of 360 pM, a 56.5% reduction of effect size could be achieved (4.09 ± 1.22 mN versus 9.41 ± 1.74 mN, P < 0.0001). Additionally, administration of 360 pM melatonin at a norepinephrine concentration of 80 mM resulted in a relaxation of 10.9 ± 2.2%. The vasodilatatory effect of melatonin was significantly reduced to 1.3 ± 0.5% when concentration of norepinephrine was doubled (P < 0.002). This study indicates that vessel segments that were exposed to thiocyanate responded with a dose-dependent vasoconstriction. The effect could be markedly attenuated in segments preincubated in melatonin.